2001
DOI: 10.1002/1521-3951(200107)226:1<1::aid-pssb1>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

The Effective Potential and Its Use in Simulation

Abstract: Quantum effects are known to occur in the channel of MOSFETs, where the confinement is in the direction normal to the oxide interface. For quite some time, there has been a desire to categorize this quantization and determine the role it plays in semiconductor devices. The questions that must be addressed in simulation are difficult. Pushing to dimensional sizes, such as sub-50 nm gate lengths, will probe the transition from classical to quantum transport, and there is no present approach to this regime that h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…For calculating the band structure of InAs, the well-established empirical pseudopotential method, which includes local, nonlocal, and spin-orbit corrections, is employed, whereas the full phonon dispersion is calculated via the valence force field model. Here, we have to mention that our simulator offers to possibility to take quantum confinement effects into account via the effective potential method [22]. However, our simulations have shown that quantum effects play only a minor role for the Device Under Test and the drain current changes only by a few percent, which is in good agreement with experimental findings [23], [24].…”
Section: A Models Usedsupporting
confidence: 85%
“…For calculating the band structure of InAs, the well-established empirical pseudopotential method, which includes local, nonlocal, and spin-orbit corrections, is employed, whereas the full phonon dispersion is calculated via the valence force field model. Here, we have to mention that our simulator offers to possibility to take quantum confinement effects into account via the effective potential method [22]. However, our simulations have shown that quantum effects play only a minor role for the Device Under Test and the drain current changes only by a few percent, which is in good agreement with experimental findings [23], [24].…”
Section: A Models Usedsupporting
confidence: 85%
“…A simplified version of this method has already been used by us to study Gaussian tunneling through a single barrier nonself-consistently [11]- [14]. Other non-WDF methods to include quantum effects have been developed, such as the effective potential [15], [16], which account for some phenomena associated with the wave-like nature of the electron but cannot account for tunneling, correlation or interference effects [17].…”
mentioning
confidence: 99%
“…The inclusion of the effective potential approach calculation in our 3D Monte Carlo particle-based simulator gives rise to an increase of the required CPU time by about 10% for both equilibrium and nonequilibrium conditions. The validity of this approach for the structure being investigated has been shown elsewhere [4].…”
Section: Introductionmentioning
confidence: 75%